New particle formation from sulfuric acid and amines: Comparison of monomethylamine, dimethylamine, and trimethylamine. Issue 13 (12th July 2017) - Olenius, Tinja; Halonen, Roope; Kurtén, Theo; Henschel, Henning; Kupiainen‐Määttä, Oona; Ortega, Ismael K.; Jen, Coty N.; Vehkamäki, Hanna; Riipinen, Ilona
Abstract: Amines are bases that originate from both anthropogenic and natural sources, and they are recognized as candidates to participate in atmospheric aerosol particle formation together with sulfuric acid. Monomethylamine, dimethylamine, and trimethylamine (MMA, DMA, and TMA, respectively) have been shown to enhance sulfuric acid‐driven particle formation more efficiently than ammonia, but both theory and laboratory experiments suggest that there are differences in their enhancing potentials. However, as quantitative concentrations and thermochemical properties of different amines remain relatively uncertain, and also for computational reasons, the compounds have been treated as a single surrogate amine species in large‐scale modeling studies. In this work, the differences and similarities of MMA, DMA, and TMA are studied by simulations of molecular cluster formation from sulfuric acid, water, and each of the three amines. Quantum chemistry‐based cluster evaporation rate constants are applied in a cluster population dynamics model to yield cluster concentrations and formation rates at boundary layer conditions. While there are differences, for instance, in the clustering mechanisms and cluster hygroscopicity for the three amines, DMA and TMA can be approximated as a lumped species. Formation of nanometer‐sized particles and its dependence on ambient conditions is roughly similar for these two: both efficiently form clusters with sulfuric acid, and cluster formation is rather insensitive to changes in temperature and relative humidity. Particle formation from sulfuric acid and MMA is weaker and significantly more sensitive to ambient conditions. Therefore, merging MMA together with DMA and TMA introduces inaccuracies in sulfuric acid‐amine particle formation schemes. Key Points: Monomethylamine, dimethylamine, and trimethylamines (MMA, DMA, and TMA) enhance H2 SO4 ‐driven particle formation but differ in their enhancing potentials Simulations indicate that clustering with H2 SO4 is efficient for DMA and TMA and weaker and more sensitive to ambient conditions for MMA DMA and TMA can be approximated as a single surrogate species, but MMA cannot be assumed to behave similarly in terms of particle formation